2020
DOI: 10.3390/molecules25112579
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystalline Copolymers Containing Sulfonic and Light-Responsive Groups: From Molecular Design to Conductivity

Abstract: In the search for novel smart multifunctional liquid crystalline materials, we report the synthesis, thermal and structural characterisation, and the conductivity, of a set of new block and statistical copolymers, containing light-responsive mesogenic groups (MeOAzB), polar sulfonic acids (AMPS), and methyl(methacrylate) groups (MMA). By using a cascade of reversible addition-fragmentation chain polymerisations, RAFT, we have tailored different side-chain polymeric structures by controlling monomer composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 86 publications
(119 reference statements)
3
11
0
Order By: Relevance
“…In some precedent works by Percec and Kato, for example, sodium, phosphonium and ammonium salts of mini-dendrons reached  dc 10 -6 to 10 -4 S cm -1 through columnar phases at room temperature [82][83][84][85]. Even though cubic phases tend to promote particularly high conductivities due to the 3D interconnectivity, lamellar LC phases promoted by rod-like molecules can also assist conductivity by reducing ionic aggregation in electrolytes [86][87][88]. Cherian et al [89] have very recently reported parallel conductivities of 10 - hydrogen sulfate.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In some precedent works by Percec and Kato, for example, sodium, phosphonium and ammonium salts of mini-dendrons reached  dc 10 -6 to 10 -4 S cm -1 through columnar phases at room temperature [82][83][84][85]. Even though cubic phases tend to promote particularly high conductivities due to the 3D interconnectivity, lamellar LC phases promoted by rod-like molecules can also assist conductivity by reducing ionic aggregation in electrolytes [86][87][88]. Cherian et al [89] have very recently reported parallel conductivities of 10 - hydrogen sulfate.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…For this reason, it is simpler to here compare UV-visible spectra to look for H-aggregation rather than only looking for studies on isomerization efficiency, however, care should be taken because often it is only a dilute solution-state absorbance spectrum of the azobenzene chromophore that is reported. 103,[126][127][128] UV-visible spectra of films of azobenzene-containing liquid crystals, where the azobenzene component is the main constituent, 129 where it is a minor dopant 130,131 and liquid crystal polymers, 132 often display spectral shifts in the p to p* excitation that are consistent with those observed for partially diluted SAMs. 92 The extent of hypsochromic shifting observed appear to trend as expected, with greater aggregate formation arising from increases in azobenzene content.…”
Section: Liquid Crystals (Lcs)mentioning
confidence: 70%
“…Despite being promising, the conductivity values obtained in this work are still two-fold smaller than benchmark ionic liquid electrolytes [98], and phosphonium or imidazolium-based ionic liquids (10 −2 S cm −1 , at 30 °C) [99]. The introduction of light responsive elements to promote local motions through reversible conformational changes [100], as well as the alignment of conductivity pathways via liquid crystalline regions [101], [102], [103], [104], will be explored as strategies to increase conductivity at low temperatures in triflimide salts derived from this study.…”
Section: Dielectric Response and Conductivitymentioning
confidence: 99%